An appraisal of result of surgery for gastric carcinoma - Khan, Zubair Afzal (International Surgery Journal, 2019)
Background: Large number of the patients with gastric carcinoma (GC) remain asymptomatic, symptoms developed only in GC with advanced lesions with local or distant metastases. GC contributes significant morbidity and mortality related to malignancy, worldwide. The objectives of this study were to study the clinical presentation, surgery type and post-operative mortality and survival in case of patients with gastric carcinoma. Methods: The study included the patients with histologically proven cases of adenocarcinoma of stomach over a period of 5 years. The study excluded the patients with proven distant metastatic disease and/or in whom only palliative surgery was performed. All the patients were followed-up regularly till 5 years after the surgery. Results: The age-group of 51-60 years had maximum number of patients with GC followed by the age-group of 41-50 years. A majority of patients were presented with epigastric pain, weight loss, and anorexia. 30 (14.22%) patients had stage I GC while 77 (36.49%) and 104 (49.29%) patients had stage II and III GC, respectively. Overall survival of the patients was 75.62%, 56.22% and 44.78% at the end of 1-year, 2-years and 5-years. Conclusions: Delayed diagnosis of gastric carcinoma responsible for this poor survival rates. The screening programs must be implemented for early diagnosis which can improve survival as well as quality of life of the patients with gastric carcinoma.